A review of developments and issues in PBL - Yee, Isabel Pin Tsin * (Sunway University, 2014)
Problem Based Learning (PBL) is a student centred educational method characterized by the use of ‘real-world’ problems as a context for students to acquire knowledge. The problems in PBL are designed to challenge students to develop effective problem-solving and critical thinking skills. This approach produces independent students who can continue to learn on their own & in their chosen careers. In PBL, teachers act as facilitators to guide the students in their problem solving efforts. The teacher poses a problem and students are encouraged to work together to define the problem and determine the best fit solution. Students are assessed on their findings by a presentation or submission of a portfolio assessment. PBL enhances learning by providing a highly motivational environment for acquisition of knowledge; students are given more responsibility for their education, it adds variety to classroom learning experience and caters for students with differing learning styles. There is considerable interest in the advantages of problem-based learning over traditional approaches. In this review, an examination of the developments and issues pertaining to problem-based learning and its educational objectives are discussed.